POCKET MALAYSIA: Learning About States in Malaysia Using Augmented Reality - Siti Fatimah Sezali; Ainun Mardhiah Radzuan; Nurul Imani Mohd Shabudin; Rabia'tul Athirah Afendi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
In era 4.0, teaching and learning are still in traditional method, which is using textbook. Hence, students become bored and easily to fall asleep during class. Therefore, researcher wish to develop an attractive and friendly-user augmented reality application as a learning aid for students. Pocket Malaysia uses AR system to learn about states in Malaysia. Student can learn in fun way through multimedia usage. There are several objectives to implement this research. Those are to identify which topic in Form One Geography Textbook is suitable to be implement in augmented reality concept, develop an augmented reality application that can help students recognize the name of states in Malaysia, location of states in Malaysia map and other details regarding each state in Malaysia through an interactive way and, evaluate usability of the application. This research uses quantitative method. The research approach is survey. About 15 students that are studying Geography subject in Universiti Pendidikan Sultan Idris (UPSI) are involve as sample through quota sampling. Overall, Pocket Malaysia is a good starting point for Geography subject in secondary school. This is because not many AR applications today are focusing on Geography subject. Based on the survey, many agree that it is easy to use although there is unclear instruction in scan section. The GUI also is quite pleasant along with the font size and colour selection. In general, it is successfully developed as it gave out the expected outcome. The weakness of this application should be improved in the future.